Penanaman Sikap Sosial dan Religius Siswa Melalui Pembelajaran IPS di Kelas V SD Negeri 1404 Batang Sosa - Siregar, Nurhayati; Daulay, Irma Sari; Siregar, Lailan Aprina; Pasaribu, Nazifah Marhani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The aim of this research is to find out how to instill students' social attitudes through social studies learning in class V of SD Negeri 1404 Batang Sosa. The type of research used is qualitative research. There are two data sources that researchers use, namely primary data sources and secondary data sources. Researchers checked the validity of the data by means of source triangulation and technical triangulation. Source triangulation is triangulation carried out by interviewing various sources, such as the school principal, homeroom teacher, fifth grade students and other teachers. The results of the research show that students' social attitudes are very good because social attitudes, namely honesty, responsibility, discipline and mutual cooperation are implemented well. So, it can be concluded that SD Negeri 1404 Batang Sosa is able to create and grow a superior generation that has good social attitudes and is embedded in students. Likewise, religious attitudes, namely humility, sincerity, tolerance and forgiveness are also implemented well. So, it can be concluded that SD Negeri 1404 Batang Sosa is able to foster a religious attitude in students